Magnetic fabric relationship between Palaeozoic volcanic and sedimentary rocks in the Nizky Jesenik Mts., NE Moravia - Hrouda,F.; Prichystal,A. (Journal of the Czech Geological Society, 1995)
Anisotropy of magnetic susceptibility (AMS) was used to investigate the fabric of magnetic minerals in Palaeozoic volcanic rocks of the Sternberk-Horni Benesov Belt in the Nizky Jesenik Mts. and in surrounding Lower Carboniferous sedimentary rocks (NE Bohemian Massif). The degree of AMS in the investigated volcanic rocks is relatively high in most specimens, clearly higher than that in recent undeformed volcanic rocks. The orientations of the magnetic fabric elements are near those in surrounding sedimentary rocks west of the Sternberk-Horni Benesov Belt, whose magnetic fabric is no doubt deformational in origin. Consequently, the magnetic fabric in the volcanic rocks investigated is deformational in origin and had at least a part of its deformational history the same as the magnetic fabric of surrounding sedimentary rocks. This conclusion is in agreement with the results of the geological research of the studied area.
Keywords: magnetic fabric; volcanic rocks; NE Moravia